Three birds with one stone: a disintegrable fertilizer with rapid fertilization, controlled-loss and detoxification - Xianghai Kong; Chen Sun; Ziyu You; Wanji Zhu; Xinxin Zhai; Yuhao Wang; Yan Wang; Weijian Zhang; Kaimin Zhu; Xiaoshuang Han; Pan Zhao; Yanping Zhu; et al. (Desalination, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Waste soy milk-derived biodegradable seed coating agent: Synthesis, growth-promotion and drought resistance - Dongqing Cai; Cun Jiang; Bingbing Fu; Shihu Shu; Dongfang Wang; Pan Zhao; Yanping Zhu (Journal of Environmental Chemical Engineering, 2026)

Long-term PFOA and cadmium Co-contamination alters soil carbon, nitrogen, and phosphorus cycling: Insights from metagenomics and metabolomics - Yanping Cai; Beihai Zhou; Shuming Liu; Chuyu Shang; Baoguo Yang; Yunqing Liu; Shengguang Zhang; Ruixue Fan; Waseem Hassan; Rongfang Yuan; Huilun Chen (Environmental Research, 2026)

Integrated transcriptomics and lipidomics provide insights into the stage-specific antifungal mechanisms of eugenol against Fusarium graminearum - Xin Yang; Luzhou Cai; Yueling Luo; Lianqun Wu; Xinyue Wang; Yanping Wu; Kai Zhong; Hong Gao (Food Bioscience, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

Folding integrated all-paper photoelectrochemical immunoassay using annealed ZnO for point-of-care detection of ferritin - Yibin Cai; Haining Li; Yanping Chen; Shuyi Lu; Huanhuan Zhu; Dianping Tang; Xiao Han; Shaofeng Lin (Analytica Chimica Acta, 2026)

Dual-ion synergistic biopolymer hydrogel: Efficient acid blue 113 adsorption with algal safety - Yanping Jia; Shuo Li; Yaoxin Hu; Jian Zhang; Fei Du; Ruixuan Cai; Lanhe Zhang (Journal of Water Process Engineering, 2026)

Lipopolysaccharide promotes rheumatoid arthritis by enhancing Wnt7b mediated macrophage-FLS communication - Bing Wang; Yingqiu Song; Wenbo Xu; Jiaqing Chen; Yurong Huang; Xinyue Zhou; Yikang Cai; Aixin Xia; Yanping Li; Liwei Jiang; Faxue Liao; Jian Huang; et al. (Inflammation Research, 2026)

Multi-level predictive group maintenance optimization method for multi-component systems: Subsea Christmas tree as a case - Yanping Zhang; Baoping Cai; Chuntan Gao; Chenyushu Wang; Yiliu Liu (Ocean Engineering, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

High pH decreases the contents of stable organic nitrogen fractions and nitrogen supply capacity by inhibiting soil organic carbon in saline-sodic paddy fields - Baishun Liu; Lihua Huang; Fengyi Zhang; Jinghui Cai; Lei Tian; Xiaotong Jiang; Yanping Liang; Ge Zhu; Guangzhi Huang (Soil and Tillage Research, 2026)

Sequential multi-objective maintenance optimization with dynamic importance ranking: A case study of subsea transportation system - Yixin Zhao; Baoping Cai; Yiliu Liu; Yanping Zhang; Shibo Wu; Gan Li (Ocean Engineering, 2026)

Local macrophage dynamics–inspired engineering of time-programmed nano-vaccine scaffold for postoperative cancer immunotherapy - Zhenyu Xu; Qian Chen; Mingyu Hao; Yiyang Cao; Xiaoqin Kuang; Chunjiayu Li; Zhihao Liu; Jiawen Xue; Jianing Zhao; Mengwei Zhao; Naicong Cai; Yiqing Li; et al. (Science Bulletin, 2026)

Macrobenthic community dynamics inform mangrove restoration practices for China - Yiyong Rao; Danyi Li; Fengxia Wu; Lizhe Cai; Shufei Zhang; Huaxue Liu; Yanping Zhong; Honghui Huang (Ocean & Coastal Management, 2026)

Hour-level humification of papermaking waste residue to produce honeycomb-like controlled-release fertilizer - Dongqing Cai; Shuang Wang; Linying Wang; Zerong Song; Yanping Zhu; Ziyu You; Jinjing Xu; Yan Wang; Wanji Zhu; Rongjun Zhang; Pan Zhao; Xiaofeng Lu; et al. (Journal of Cleaner Production, 2026)

Preparation of sawdust-based degradable mulch film and nutrient slow-release performance evaluation - Xianghai Kong; Rongxi Hu; Zerong Song; Xinxin Zhai; Ziyu You; Yuhao Wang; Pan Zhao; Xiaofeng Lu; Rongjun Zhang; Yanping Zhu; Dongfang Wang; Dongqing Cai (Journal of Environmental Chemical Engineering, 2026)

One-step microwave fabrication of waste potato-derived bifunctional film: sustainable mulch-fertilizer for plastic substitution - Dongqing Cai; Weijia Liu; Dongfang Wang; Shihu Shu; Pan Zhao; Tao Zhang; Yi Qiao; Xiaoshuang Han; Weijian Zhang; Kaimin Zhu; Rongjun Zhang; Yanping Zhu (Environmental Research, 2026)

A synergistic maintenance optimization method driven by integrated-resilience: Subsea Christmas tree as a case - Yanping Zhang; Baoping Cai; Chuntan Gao; Chenyushu Wang; Zhaoyi Pan; Zhen Qin (Ocean Engineering, 2025)

Fabrication of a nonwoven fabric-based multifunctional mulch film with Cr(VI) remediation capacity - Dongqing Cai; Jinjing Xu; Jiangshan Li; Xianghai Kong; Maowei Wu; Yan Wang; Wanji Zhu; Pan Zhao; Xiaofeng Lu; Xiaoli Tang; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2025)

Enhanced dehydrogenation kinetics and cyclic stability of NaAlH4 through nitrogen coupling with Ti3C2 MXene - Zhenluo Yuan; Ruyi Guo; Xiuxiu Zhang; Jiabao Cai; Haiwen Li; Qiuming Peng; Shumin Han; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2025)

Valorizing industrial and agricultural wastes into a high-performance composite for remediation of heavy metal-contaminated tailing sands - Mengjia Liang; Man Xue; Yanping Shi; Jihua Cai; Xianyu Yang; Chunzheng Jin; Zexin Chen; Maoyan Xu (Environmental Research, 2025)

Treating waste with waste: 1 h deep-drying of sewage sludge by secondary aluminum ash - Xianghai Kong; Zerong Song; Jie Wu; Ziyu You; Xiaofeng Lu; Bin Huang; Rongjun Zhang; Xiaoshuang Han; Xuemei Yu; Weijian Zhang; Yanping Zhu; Dongfang Wang; et al. (Journal of Cleaner Production, 2025)

Honeycomb-like slow-release fertilizer based on drinking water treatment sludge - Yanping Zhu; Shaofeng Dun; Yajuan Li; Tao Zhang; Xianghai Kong; Xiaomeng Han; Shihu Shu; Dongfang Wang; Weigang Wang; Cun Jiang; Kaili Li; Dongqing Cai (Journal of Environmental Chemical Engineering, 2025)

Bioaugmentation with Caldibacillus thermoamylovorans improved methane production of thermophilic anaerobic digestion via enhancing hydrolysis and acidification processes - Mengyao Xiao; Na Wang; Lin Xu; Dongqing Cai; Yanping Zhu; Jiping Shi; Siying Zhang; Li Liu (Journal of Environmental Chemical Engineering, 2025)

Electron beam/persulfate-induced second-scale upcycling of wastewater polyvinyl alcohol with ultra-low chemical input - Tao Zhang; Yanping Zhu; Yongle Yu; Xiaoya Pan; Pan Zhao; Shihu Shu; Dongfang Wang; Jiping Shi; Li Liu; Weijian Zhang; Bin Huang; Xiaofeng Lu; et al. (Water Research, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Dust supply to the West Philippine Sea since the Middle Pleistocene and distinct influences of the Westerlies after the Mid-Brunhes Event - Yun Cai; Dong Xu; Haifeng Wang; Yanping Chen; Haiyan Jin; Yibing Li; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Treatment of kiwifruit with Lactiplantibacillus pentosus CW5 cell-free supernatant maintains postharvest quality and alters the surface microbiome - Yuxuan Hao; Huili Pang; Haoxin Lv; Guofang Wu; Jianbo Zhang; Xuan Luo; Miao Zhang; Yaoke Duan; Yuting Hou; Yanping Wang; Lei Wang; Yimin Cai; et al. (Postharvest Biology and Technology, 2025)

Fabrication of biodegradable mulch film based on polylactic acid waste liquid - Dongfang Wang; Zerong Song; Xianghai Kong; Jie Wu; Jinjing Xu; Jinghong Ye; Yanping Zhu; Rongjun Zhang; Xiaoli Ma; Gang Li; Shifang Xu; Dongqing Cai (Chemical Engineering Journal, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

The application of amendments improves properties of salt-affected soils across China - Guangzhi Huang; Baishun Liu; Xiaotong Jiang; Yanping Liang; Jinghui Cai; Lihua Huang (Soil and Tillage Research, 2025)

Biosynthetic small molecule antigens mimics medicated lateral flow immunoassay for mycotoxin Fumonisin B1 using nanobody fusion proteins - Chong Cai; Yuheng Xia; Yuanzhen Guo; Binhui Huang; Tailong Wei; Yun Liang; Qiannan Gao; Zhui Tu; Yanping Li; Qinghua He (Journal of Hazardous Materials, 2025)

Interpretation of the Budyko framework for monthly evapotranspiration prediction of individual basins - Hao Sun; Xingwang Wang; Yanping Qu; Juan Lyu; Hehe Cai; Xuejun Zhang (Atmospheric Research, 2025)

Enhanced fermentation of radish paocai with Lactiplantibacillus plantarum CBPC and shelf-life extension using e-beam irradiation - Ling Li; Qian Zhou; Zimeng Zheng; Luzhou Cai; Yanping Wu; Kai Zhong; Hong Gao (Food Bioscience, 2025)

Mass mortality associated with carpione rhabdovirus in golden pompano (Trachinotus ovatus) in China: First report - Heng Sun; Jie Huang; Haoyu Wang; Yule Zhang; Qing Fei; Jie Zhou; Lindi Yang; Yanping Li; Jichang Jian; Yishan Lu; Shuanghu Cai; Yucong Huang (Aquaculture, 2025)

Multiple-cation doped LaCl3-based chloride solid-state electrolyte compatible with lithium metal - Xuxia Hao; Kai Chen; Min Jiang; Yanping Tang; Yuexin Liu; Kefeng Cai (Chemical Engineering Journal, 2025)

Analysis of molecular identity and function of putative serotonin receptors in the Giant clam (Tridacna crocea) and the potential role of 5-HT1D-like receptor in reproduction - Xiaogang Yang; Zohaib Noor; Shuming Guo; Zhen Zhao; Borui Cai; Guozhao Huang; Haitao Ma; Yanping Qin; Ziniu Yu; Jun Li; Yuehuan Zhang (Aquaculture, 2024)

A solar thermoelectric system by temperature difference for efficient removal of chromium (VI) in water and soil - Dongqing Cai; Rongxi Hu; Minxue Guo; Dongfang Wang; Yanping Zhu; Chen Sun; Xinyan Chen; Jinghong Ye; Xianghai Kong; He Xu (Journal of Hazardous Materials, 2024)

Sedimentary dynamics in southern Mariana Trench and its controlling factors in past 440 kyr - Zhongshan Shen; Haifeng Wang; Yanping Chen; Yun Cai; Liang Yi (Frontiers in Marine Science, 2024)
Understanding sediment dynamics and their controlling factors is essential for Quaternary studies, yet they remain poorly documented in the Mariana Trench. In this work, we examine this basic character from a sediment core collected at a depth of 6470 m from the southern part of the Mariana Trench, documenting changes in sedimentary dynamics over the past ~440 kyr. Our primary findings are as follows: (1) The median grain size is 13.6 ± 12.0 μm, and minimal changes in clay (30.9 ± 9.4%) and silt (56.6 ± 4.0%) contents, indicating a low-dynamic depositional environment; (2) Three grain-size components were identified, characterized by modal changes of ~4/60 μm, ~20 μm, and >100 μm. By comparing these results with various environmental proxies, including glacial-interglacial alternations, eolian input, and bottom-water intensity, we suggest that marine productivity has a dominant influence on deep-sea sediment dynamics, though post-depositional processes also contribute. Additionally, topographical conditions and sea-water chemistry appear to be related to the presence of coarse particles, possibly through coarse transport and micro-nodule development. Overall, grain-size parameters provide a valuable investigative tool for understanding the various influences on sediment dynamics in this region.

Three birds with one stone: Sewage sludge deep-drying in 1 hour using secondary aluminum ash to fabricate bricks - Xianghai Kong; Yanping Zhu; He Xu; Jinghong Ye; Shuang Wang; Heliang Xu; Rongjun Zhang; Hongxia Tang; Dongfang Wang; Dongqing Cai (Water Research, 2024)

A life cycle reliability testing and assessment method for deepwater oil and gas equipment systems - Chuntan Gao; Baoping Cai; Yanping Zhang; Xiaoyan Shao; Chao Yang; Lei Gao (Ocean Engineering, 2024)

Early diagenesis, sedimentary dynamics and metal enrichment reveal deep-sea ventilation in Magellan Seamounts during the middle Pleistocene - Zhongshan Shen; Yanping Chen; Pavel Mikhailik; Yun Cai; Haifeng Wang; Liang Yi (Frontiers in Marine Science, 2024)
Seamounts are ubiquitous topographic units in the global oceans, and the Caiwei Guyot in the Magellan Seamounts of the western Pacific is a prime example. In this study, we analyzed a well-dated sediment core using magnetic properties, sediment grain size, and metal enrichment to uncover regional ventilation history during the middle Pleistocene and explore potential linkages to global climate changes. Our principal findings are as follows: (1) The median grain size is 3.3 ± 0.2 μm, and clay and silt particles exhibit minimal variation, with average values of 52.8 ± 1.8% and 38.2 ± 1.6%, respectively, indicating a low-dynamic process; (2) Three grain-size components are identified, characterized by modal patterns of ~3 μm (major one), ~40 μm, and 400–500 μm, respectively; (3) Magnetic coercivity of the deep-sea sediments can be classified into three subgroups, and their coercivity values are 6.1 ± 0.5 mT, 25.7 ± 1.0 mT, and 65.2 ± 2.1 mT. Based on these results, we propose a close linkage between magnetic coercivity and metal enrichment, correlating with changes in deep-sea circulation intensity. Conversely, sediment grain-size changes seem to be more strongly influenced by eolian inputs. Consequently, we suggest that regional ventilation has weakened since ~430 ka, likely linked to a reduction in Antarctic bottom water formation.

New role of radical-induced polymerization: Base/self-heating synergistically activate persulfate to boost food waste humification - Dongqing Cai; Xiaoya Pan; Chengjin Wang; Shihu Shu; Pengjin Zhu; Chunhuo Zhou; Dongfang Wang; He Xu; Yanbiao Liu; Wenhai Chu; Xiang Li; Yanping Zhu (Journal of Cleaner Production, 2024)

Waste milk-derived biodegradable mulch film fabrication and nutrient slow-release performance evaluation - Yanping Zhu; Bingbing Fu; Pengjin Zhu; Shihu Shu; Dongfang Wang; He Xu; Dongqing Cai (Chemical Engineering Journal, 2024)

Ginsenoside Rg1 treats chronic heart failure by downregulating ERK1/2 protein phosphorylation - Liqi Peng; Shaodong Li; Huzhi Cai; Xueliang Chen; Yanping Tang (In Vitro Cellular & Developmental Biology - Animal, 2024)

Condition-based maintenance method for multi-component systems under discrete-state condition: Subsea production system as a case - Rongkang Li; Baoping Cai; Yixin Zhao; Yiliu Liu; Yanping Zhang; Xiangdi Kong; Yonghong Liu (Ocean Engineering, 2024)

Simultaneous removal of tetracycline hydrochloride and hexavalent chromium by heterogeneous Fenton in a photocatalytic fuel cell system - Jinghong Ye; He Xu; Xianghai Kong; Yong Zhang; Yuhan Chen; Benji Zhou; Yanping Zhu; Dongqing Cai; Dongfang Wang (Journal of Environmental Management, 2024)

Quantitative evaluation and mechanism analysis of soil chemical factors affecting rice yield in saline-sodic paddy fields - Baishun Liu; Lihua Huang; Xiaotong Jiang; Ying Liu; Guangzhi Huang; Can Yang; Yanping Liang; Jinghui Cai; Ge Zhu; Qianqian Kong (Science of The Total Environment, 2024)

Correction to: Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

Fabrication of a straw-based degradable mulch film with magnetically controlled-release glyphosate - Dongqing Cai; Mengjia Cui; Linying Wang; Jinghong Ye; Xianghai Kong; Ruobing Mu; He Xu; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2024)

Identification and characterization of Achromobacter spanius P-9 and elucidation of its deoxynivalenol-degrading potential - Feng Yao; Yaowen Du; Siyi Tian; Guoli Chang; Yanping Zhang; Ruiyu Zhu; Chenggang Cai; Suqin Shao; Ting Zhou (Archives of Microbiology, 2024)

Strategies for deoxynivalenol (DON) degradation by microbes from organic fertilizers and influence of the bacterial diversity after DON treatment - Feng Yao; Yaowen Du; Siyi Tian; Guoli Chang; Yanping Zhang; Chenggang Cai; Ruiyu Zhu; Suqin Shao; Ting Zhou (International Biodeterioration & Biodegradation, 2024)

Associations between residential greenness and asthma and allergic rhinitis in children: A systematic review and meta-analysis - Wei Liu; Kailun Liu; Jiao Cai; Shuang Ma; Minghan Yang; Quan Yang; Yanping Yuan (Sustainable Cities and Society, 2023)

First kinetics verification of the useful H2Ogas inhibition on the thermal regeneration of spent activated carbon in flue gas desulfurization - Hanyu Deng; Wenzhen Cai; Lanhe Zhang; Yanping Jia; Xiaoqiang Wang; Qing Zong; Guishi Cheng; Xiaoying Hu; Changqing Dong; Ying Zhao (Fuel, 2023)

S-scheme MIL-101(Fe) octahedrons modified Bi2WO6 microspheres for photocatalytic decontamination of Cr(VI) and tetracycline hydrochloride: Synergistic insights, reaction pathways, and toxicity analysis - Shijie Li; Chunchun Wang; Yanping Liu; Yazi Liu; Mingjie Cai; Wei Zhao; Xiaoguang Duan (Chemical Engineering Journal, 2023)

Hyperspectral anomaly detection based on score-guided cooperative autoencoders - Minkai Hou; Tao Wang; Yanzhao Su; Yanping Cai; Yiting Wang (International Journal of Remote Sensing, 2022)

Hyperspectral anomaly detection based on adaptive weighting method combined with autoencoder and convolutional neural network - Minkai Hou; Tao Wang; Yanzhao Su; Yanping Cai; Jiping Cao (International Journal of Remote Sensing, 2022)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

Identification and characterization of PaGL1-like genes from Platanus acerifolia related to the regulation of trichomes - Yanping Zhang; Changsheng Shao; Zhiru Bao; Fangfang Cai; Haofei Zhu; Jiaqi Zhang; Manzhu Bao (Plant Molecular Biology, 2020)

Improving N management through intercropping alleviates the inhibitory effect of mineral N on nodulation in pea - Falong Hu; Cai Zhao; Fuxue Feng; Qiang Chai; Yanping Mu; Yan Zhang (Plant and Soil, 2017)

Four SQUAMOSA PROMOTER BINDING PROTEIN-LIKE homologs from a basal eudicot tree (Platanus acerifolia) show diverse expression pattern and ability of inducing early flowering in Arabidopsis - Hongji Han; Guofeng Liu; Jiaqi Zhang; Sisi Zhang; Fangfang Cai; Zhiru Bao; Yanping Zhang; Manzhu Bao (Trees, 2016)